2017
DOI: 10.1136/bmjopen-2016-013115
|View full text |Cite
|
Sign up to set email alerts
|

Single-visit or multiple-visit root canal treatment: systematic review, meta-analysis and trial sequential analysis

Abstract: ObjectivesSingle-visit root canal treatment has some advantages over conventional multivisit treatment, but might increase the risk of complications. We systematically evaluated the risk of complications after single-visit or multiple-visit root canal treatment using meta-analysis and trial-sequential analysis.DataControlled trials comparing single-visit versus multiple-visit root canal treatment of permanent teeth were included. Trials needed to assess the risk of long-term complications (pain, infection, new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 54 publications
6
42
1
16
Order By: Relevance
“…However, a correlation between single visit and flare-ups has been shown in the past. [ 18 19 20 ] Hence, in the present study, we compared single visit and multiple visit endodontics and found no significant difference in flare-up rates between them which is in agreement with the majority of studies. [ 1 4 12 21 ]…”
Section: Discussionsupporting
confidence: 90%
“…However, a correlation between single visit and flare-ups has been shown in the past. [ 18 19 20 ] Hence, in the present study, we compared single visit and multiple visit endodontics and found no significant difference in flare-up rates between them which is in agreement with the majority of studies. [ 1 4 12 21 ]…”
Section: Discussionsupporting
confidence: 90%
“…Except for the study by Paredes-Vieyra & Enriquez [50], which presented a significant risk (odds ratio of 3.5) in favour of single-visit endodontics, all other included studies showed no significant difference between the treatment modalities. The same finding was reported in a meta-analysis by Schwendicke & Gostemeyer [44]. In this study, the aim was to study several factors such as pain and flare-ups related to one-visit versus multiple-visit root canal treatment.…”
supporting
confidence: 66%
“…In general, different studies have evaluated finishing root canal treatment in a one visit or more. The clinicians can complete the treatment in one or multiple visits [14]. There is no evidence suggesting that it is better to complete the root canal treatment in a single visit or in multiple visits [15].…”
Section: Discussionmentioning
confidence: 99%